Attention, Not Self - Ganeri, Jonardon (Oxford University Press, 2017)
Attention is of fundamental importance in the philosophy of mind, in epistemology, in action theory, and in ethics. This book presents an account in which attention, not self, explains the experiential and normative situatedness of human beings in the world. Attention consists in an organization of awareness and action at the centre of which there is neither a practical will nor a phenomenological witness. Attention performs two roles in experience, a selective role of placing and a focal role of access. Attention improves our epistemic standing, because it is in the nature of attention to settle on what is real and to shun what is not real. When attention is informed by expertise, it is sufficient for knowledge. That gives attention a reach beyond the perceptual: for attention is a determinable whose determinates include the episodic memory from which our narrative identities are made, the empathy for others that situates us in a social world, and the introspection that makes us self-aware. Empathy is other-directed attention, placed on you and focused on your states of mind; it is akin to listening. Empathetic attention is central to a range of experiences that constitutively require a contrast between oneself and others, all of which involve an awareness of oneself as the object of another’s attention. An analysis of attention as mental action gainsays authorial conceptions of self, because it is the nature of intending itself, effortful attention in action, to settle on what to do and to shun what not to do.